SELF-REGULATED LEARNING STRATEGIES AND THEIR RELATIONSHIP TO GRAMMAR ACHIEVEMENT OF UNDERGRADUATE ENGLISH DEPARTMENT STUDENTS - Wardani, Andini Dwi; Munir, Ahmad; Lestari, Lies Amin; Anam, Syafi'ul (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Self-regulated learning is an educational process that enables students to self-regulate when determining ideas or concepts and evolving their learning strategies to accomplish attainable outcomes. The present study investigated self-regulated learning strategies undergraduate English department students used and examined the significant relationship with students' grammar achievement. The researchers conducted a quantitative correlational design on 70 undergraduate English department students. The researchers collected the data through a self-regulated learning strategies questionnaire and students' grammar scores. The first result showed that the peer learning strategy was the dominant strategy used by students with the highest average score (M= 3.48, SD= 1.14), and the less dominant strategy with the lowest average score is time and study environment (M= 3.03, SD= 0.99). This study applied descriptive statistics using the SPSS program to describe the first research problem. The second result was analyzed using Pearson correlation, indicating a low negative correlation between self-regulated learning strategies and students' grammar achievement. Thus, this study concluded that the higher the grammar achievement students' got, the less self-regulated learning strategies they used, and the less grammar achievement students' got, the more learning strategies they used.